Vessel Size and Long-Term Outcomes After Limus-Based Drug-Eluting Stent Implantation Focusing on Medium- and Small-Diameter Vessels. (July 2017) - Hsieh, I-Chang; Hsieh, Ming-Jer; Chang, Shang-Hung; Wang, Chao-Yung; Lee, Cheng-Hung; Yang, Chia-Hung; Chen, Dong-Yi; Tsai, Ming-Lung; Chen, Chun-Chi
Introduction: This study aimed to evaluate the efficacy and safety of limus-based drug-eluting stent (DES) implanted in medium or small coronary vessels during a very long-term follow-up period. Methods: A total of 2383 patients treated with 2916 limus-based DES between April 2003 and March 2015 were evaluated. The enrolled patients were stratified into 3 groups according to the reference vessel diameter: group A: ≤2.5 mm; group B: 2.51 to 3.00 mm; group C: 3.01 to 3.50 mm. Results: Group A had a significantly higher loss index and binary restenosis rate than the other 2 groups at 9 months of angiographic follow-up. Group A also had a significantly higher rate of target lesion revascularization and a lower rate of major adverse cardiovascular event–free survival than the other 2 groups after a follow-up period of 68 ± 59 months. The long-term cardiovascular event–free survival curves based on a Cox regression model showed large vessel size, and second-generation DES had better outcomes. Conclusion: An inverse relationship between vessel size (≤3.5 mm) and clinical outcomes was noted in patients who received limus-based DES implantation.